VISUALIZATION OF ANTENNA’S PARAMETERS SIMULATED WITH NEC-2 - Chaber, Bartosz (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2013)
Article presents information about visualization of data output from NEC-2. Authors describes their own tools used for visualization of antenna’s parameters like radiation pattern, wave impedance, ?11 parameter.